Análise da região do anel v de Urano - Moura, Vanessa Maria Francisco de [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Since 2012, it's know the mechanism responsible for the existence of the Uranian ring (Sfair GiuliattiWinter, 2012). The maintenance of this ring is accomplished through the ejection of dust particles from the Mab satellite, due to collisions of this satellite with interplanetary projectiles, with sizes of the order of micrometres. Due to the effects of solar radiation and flattening of the planet Uranus, these particles evolve over time populating the ring. The purpose of this work was to study the naked ring of Uranus, since the mechanism responsible to maintain this ring around Uranus is still unknown. Therefore, our purpose is to investigate a possible mechanism of maintenance of the ring population using hypothetical satellites immersed in the ring. In addition, we will estimate the generation and removal of dust particles from possible collisions between hypothetical satellites and satellites (Portia and Rosalinda), or between interplanetary projectiles

Desde 2012 é conhecido o mecanismo responsável pela existência do anel de Urano (Sfair & Giuliatti Winter, 2012). A manutenção desse anel é realizada por meio da ejeção de partículas de poeira do satélite Mab, devido a colisões deste satélite com projéteis interplanetários, com tamanhos da ordem de micrometros. Devido aos efeitos de radiação solar e do achatamento do planeta Urano, essas partículas evoluem ao longo do tempo populando o anel . O intuito deste trabalho foi o de estudar o anel de Urano, já que o mecanismo responsável por manter este anel em torno de Urano ainda é desconhecido. Portanto, nosso propósito é investigar um possível mecanismo de manutenção da população do anel utilizando satélites hipotéticos imersos no anel. Além disso, iremos estimar a geração e remoção de partículas de poeira a partir de possíveis colisões entre os satélites hipotéticos e os satélites envolvidos (Portia e Rosalinda), ou entre projéteis interplanetários
Analysis of the region of the v ring of Uranuss
Keywords: Planetas; Satelites; Projéteis; Planets